Sex-Related Differences in Heart Failure Development in Patients After First Myocardial Infarction: The Role of Galectin-3 - Milica Dekleva; Tamara Djuric; Ana Djordjevic; Ivan Soldatovic; Aleksandra Stankovic; Jelena Suzic Lazic; Maja Zivkovic (Biomedicines)
Backgrounds: Galectin-3 (gal-3) is upregulated in remodeling, and failing myocardium and gal-3 levels are increased in hypertrophy, fibrosis and inflammation. The aim of this study was to investigate the potential role of sex-related differences in the following: risk factors, left ventricular (LV) structural and functional changes, coronary angiography, expression of the gal-3 encoding gene LGALS-3 and plasma gal-3 levels in heart failure (HF). Materials and Methods: This prospective study included 137 men and 44 women with first MI who underwent Doppler echocardiography within 2–4 days of MI and after 6 months. Relative LGALS-3 mRNA expression in peripheral blood mononuclear cells (PBMCs) was detected using TaqMan® technology. Plasma gal-3 concentration was determined by ELISA method. Results: In the acute phase of MI, LV end-diastolic and end-systolic volume indexes (LVEDVI and LVESVI) were significantly lower in women compared to men (58.2 ± 13.1 vs. 46.3 ± 11.1, p < 0.001; 33.7 ± 9.5 vs. 27.0 ± 9.2, p < 0.001, respectively). The incidence of LV hypertrophy (LVH) and HF was significantly higher in women compared to men (70.0% vs. 44.6%, p = 0.03; 37.5% vs.19.5%, p = 0.02, respectively). There was a significant correlation between the grade of LV diastolic dysfunction (LVDD) and plasma gal-3 levels (p < 0.001). The relative expression of LGALS-3 mRNA in PBMCs was higher in females (fold induction = 1.326, S.E. range = 0.748–2.587, p = 0.007). Plasma gal-3 levels were higher in women compared to men (44.66 ± 28.04 vs. 16.30 ± 12.68, p < 0.001) and higher in patients with HF than in patients without HF (31.14 ± 27.09 vs.21.39 ± 18.17, p = 0.025). Conclusions: Gender-specific factors such as LVH, LVDD, LGALS-3 mRNA expression and plasma gal-3 levels may explain the increased incidence of HF in women. The differences in the model and determinants of HF between men and women may be relevant for further therapeutic strategies including the inhibition of gal-3.